Intellectual Capital dan Modal Sosial Dalam Mendorong Kinerja Perusahaan - Ni Nyoman Ayu Suryandari; Gde Bagus Brahma Putra; Ni Nyoman Novia Pratiwi (Juara: Jurnal Riset Akuntansi, 2021)
This study examines intellectual capital and social capital in encouraging company performance. Companies are not able to win the competition only by relying on tangible assets. OJK stated that in the fourth quarter of Indonesia's banking performance decreased, the ROA of the banking industry in December 2014 was 2.85 and in November 2015 it was 2.30. Weak human resource competencies where the company only focuses on optimizing tangible resources but does not pay attention to intellectual capital and social capital in creating competitive advantage capabilities for the company. used a number of 42 banking companies on the Indonesia Stock Exchange obtained based on purposive sampling technique. With multiple linear regression analysis, the results showed that the variables of human capital, structural capital, customer capital and social capital were able to improve company performance.